The quest for drug control : politics and federal policy in a period of increasing substance abuse, 1963-1981 - Musto, David F., 1936-2010 (Yale University Press, 2002)
Between 1960 and 1980 various administrations attempted to deal with a rising tide of illicit drug use that was unprecedented in U.S. history. This book provides a close look at the politics and bureaucracy of drug control policy during those years, showing how they changed during the presidencies of Johnson, Nixon, Ford, and Carter and how much current federal drug-control policies owe to those earlier efforts.